Aging, human immunodeficiency virus, and bone health - Kim C Mansky (Dove Medical Press, 2010)
Kim C ManskyDivision of Orthodontics, Department of Developmental and Surgical Sciences, School of Dentistry, University of Minnesota, Minneapolis, MN, USAAbstract: Highly active antiretroviral therapy (HAART) has had a profound impact on improving the long-term prognosis for individuals infected with human immunodeficiency virus (HIV). HAART has been available for close to two decades, and now a significant number of patients with access to HAART are over the age of 50 years. Many clinical studies have indicated that HIV infection, as well as components of HAART, can increase the risk in these individuals to a variety of noninfectious complications, including a risk to bone health. There is a significant need for detailed mechanistic analysis of the aging, HIV-infected population regarding the risk of HIV infection and therapy in order to maintain bone health. Insights from basic mechanistic studies will help to shed light on the role of HIV infection and the components of HAART that impact bone health, and will help in identifying preventative countermeasures, particularly for individuals 50 years of age and older.Keywords: osteopenia, osteomalacia, osteoporosis, bisphosphonates, tenofovir, osteoimmunology